GURSA TASKS FOR ONE EQUATION OF THE FOURTH ORDER WITH SINGULYAR COEFFICIENTS (Scientific journal of the Fergana State University, 2023)
In the paper an analogue of the Gursat problem was investigated for a non classical fourth order partial equation with singular coefficients. To solve the problems, we applied the two-dimensional generalized Erdeyi-Kober operator. The solution is shown explicitly.